Reactive Oxygen Species - Ahmad, Rizwan (Biochemistry, 2022)
The term "reactive oxygen species" (ROS) refers to a group of reactive molecules and free radicals produced by molecular oxygen. In recent decades, there has been great interest in the role of ROS in various diseases. From basic science research to clinical trials, biomedical scientists have made rapid progress toward a better understanding of ROS-metabolizing systems and their role in health and diseases. This book includes sixteen chapters that address topics such as the history of ROS, its role in autoimmunity, neurodegeneration, and aging, and recent advances in various antioxidants and their therapeutic potential.